ETHICAL CHALLENGES OF THE E-LEARNING SYSTEM - MARIA CERNAT (Challenges of the Knowledge Society, 2013)
This article is the result of a four years teaching experience in one of the largest and controversial Romanian Universities using the E-learning system: Spiru Haret. It is a well-known fact that this was the first Romanian academic institution that used the E-learning techniques in wide and systematic way. Numerous articles appeared in the press in 2009 when the scandal of fake diplomas first started. This article is the perspective of an insider, that is, of someone who taught information and communication techniques in this institution for several years. I consider my experience and my findings to be balanced and objective and I also believe that we have to analyze things in a more profound and rational manner after the 2009 media storm ended. My article provides very useful information in this area since there are no academic articles on the way this Romanian academic institution (mis)understands the power of E-learning tools.